Analisa Pembengkokan Pelat dengan Metode Line Heating - Pardi Pardi; Romadhoni Romadhoni; Budhi Santoso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
One method of bending the plates in hull construction can be done either by conventional or by line heating method. The method of line heating has several advantages, such as lesser initial investment and can be used for three dimension form. This research is focused to obtain the relation between the parameter in line heating process and the conceited of plate curve that produced. With the aim of the curvature of structural changes caused by the heat given during the plate bending process it can be seen for the shipbuilding fabrication process. From the results of this study obtained data on line heating conditions on plates with a thickness of 10 mm (plates A and B) obtained the maximum curvature height is 11.1 mm at a heating speed of 8 mm / s and a heating temperature of 3850 C. Furthermore, the amount of heat input that is applied to material 3327.47 Joules / sec and due to efficiency at 1697,001 Joules / sec. Keyword: Line Heating Method, Line Heating Parameter, Curve Heights